Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
Step-by-step explanation:
this is okay ... use the point-slope formula [y-y1=m(x-x1)] with your given point.. also m is the slope.. which as is.. is undefined.. so just leave it like that.. the teacher is making this too abstract thou.. to make sense
y-2=m(x-(-3))
y-2 = m(x+3)
y-2 = mx +3m
y = mx +3m +2
that's all you could do for now.. until the slope is defined :)
Answer:
y-2=m(x-(-3))
y-2 = m(x+3)
y-2 = mx +3m
y = mx +3m +2
Step-by-step explanation:
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.